The role of L-type amino acid transporters in the uptake of glyphosate across mammalian epithelial tissues. (February 2016) - Xu, Jiaqiang; Li, Gao; Wang, Zhuoyi; Si, Luqin; He, Sijie; Cai, Jialing; Huang, Jiangeng; Donovan, Maureen D.
Abstract: Glyphosate is one of the most commonly used herbicides worldwide due to its broad spectrum of activity and reported low toxicity to humans. Glyphosate has an amino acid-like structure that is highly polar and shows low bioavailability following oral ingestion and low systemic toxicity following intravenous exposures. Spray applications of glyphosate in agricultural or residential settings can result in topical or inhalation exposures to the herbicide. Limited systemic exposure to glyphosate occurs following skin contact, and pulmonary exposure has also been reported to be low. The results of nasal inhalation exposures, however, have not been evaluated. To investigate the mechanisms of glyphosate absorption across epithelial tissues, the permeation of glyphosate across Caco-2 cells, a gastrointestinal epithelium model, was compared with permeation across nasal respiratory and olfactory tissues excised from cows. Saturable glyphosate uptake was seen in all three tissues, indicating the activity of epithelial transporters. The uptake was shown to be ATP and Na + independent, and glyphosate permeability could be significantly reduced by the inclusion of competitive amino acids or specific LAT1/LAT2 transporter inhibitors. The pattern of inhibition of glyphosate permeability across Caco-2 and nasal mucosal tissues suggests that LAT1/2 play major roles in the transport of this amino-acid-like herbicide. Enhanced uptake into the epithelial cells at barrier mucosae, including the respiratory and gastrointestinal tracts, may result in more significant local and systemic effects than predicted from glyphosate's passive permeability, and enhanced uptake by the olfactory mucosa may result in further CNS disposition, potentially increasing the risk for brain-related toxicities. Highlights: Transport properties of glyphosate were investigated using Caco-2 and nasal mucosal tissues. Inhibitors were used to investigate the role of LAT transporters in glyphosate permeation in both tissues. Glyphosate permeation across both epithelia is mediated by amino acid transporters.